A second species of the genus Sturmius BRETFELD, 1994: Sturmius truncivivus n.sp. from Brazil (Insecta, Collembola, Symphypleana) - Bretfeld, Gerhard; Gauer, Ulrich (Amazoniana, 1999)
From Manaus, Brazil, AM, Sturmius truncivivus n.sp. is described. It is the second species of this remarkable genus, which is known from Colombia and shows an unusual combination of characteristics. This new species lives on trees, as does the type species, but has not been collected from epiphytes but by trunk traps.
Keywords: Sturmius Truncivivus